Tragacanth gum mediated green fabrication of mesoporous titania nanomaterials: Application in photocatalytic degradation of crystal violet - Mallakpour, Shadpour; Ramezanzade, Vahid (Journal of environmental management, 2021)
Water remediation is a crucial subject in present century. Hence, several processes have been used for this aim, which the photodegradation method with high activity, cost-effectiveness, and durability has been remarkable. In this project, the various novel mesoporous Titania nanomaterials (MTN) were green synthesized using Tragacanth gum as coupling agent. The effect of calcination times on the crystalline structure of the resulted MTNs was examined. MTNs displayed the dramatically specific surface area with negative surface charge and nano-sheet structure, and they applied for photodegradation of crystal violet under ultraviolet irradiation due to proper band gaps energy. The obtained MTN in 8 h calcination time (MTN-8) showed the best photoreduction activity. Also, the superoxide radicals, electrons, and hole pairs represented the main degradation agents as the reduction rate of crystal violet. Next, the transformation pathways were proposed, which could be transformation singlet oxygen addition, hydroxyl addition, and N-demethylation reactions. [Display omitted] •MTNs were green synthesized using TG polysaccharides as capping and reducing agent.•TG mediated synthesized MTNs had high specific surface area.•Influence of calcination holding time was studied on MTNs' crystallinity.•Superoxide radicals had key role in photocatalytic activity of MTN-8.•The degradation pathway of CV was proposed over MTN-8.